Sosiodemografi Memoderasi Pemahaman Masyarakat Dengan Mendeterminasi Terhadap Minat Investasi di Pasar Modal (Studi Kasus : Masyarakat Kota Medan) - Jeroh Miko; Talia Yudrieka (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
Investment is something that is usually done by every individual, both in real assets and financial assets. Financial assets in the capital market, such as buying stocks or bonds, are something new for Indonesians to invest in compared to other countries that have developed very rapidly. The reason for the lack of public interest in investing in the capital market is due to the lack of knowledge about investment in this sector. This study aims to further examine sociodemographic factors as moderating variables that determine the interest of the people of Medan in investing in the capital market. The analysis technique of Moderated Regression Analysis (MRA) is a data analysis technique used in this study. The results of this study were conducted at a level of 5% which states that partially knowledge and sociodemography have a positive effect, while perception has no effect. In addition, sociodemography moderates by weakening the relationship between knowledge and public interest in investing in the capital market, while sociodemography moderates by strengthening the relationship between perceptions of people's interest in investing in the capital market. Meanwhile, simultaneously each variable influences people's interest in investing in the capital market.